ANALISIS KINERJA KEUANGAN PT. INDO RAMA SYNTHETICS TBK. - PASRIZAL, HIMYAR HIMYAR; OKTARIA, RINA RINA; YENTI, ELFINA ELFINA (IAIN Batusangkar, 2017)
The research problem was on the unknown quality of ?inancial performance of PT. Indo RamaSynthetics, Tbk in the form of the ratio of liquidity. Then, the purpose of the research was to analyze the?inancial performance of PT. Indo Rama Synthetics, Tbk in the form of the ratio of liquidity, solvency,activity, and pro?itability. Descriptive quantitative was used as the design of the research. The setting ofthe research itself was at PT. Indo Rama Synthetics, Tbk 2011 ? 2015 period listed on IDX. It could alsobe accessed through website www.idx.co.id. The research itself was done during May to June, 2016. Thedata of the research were ?inancial reports. The ?indings re?lected that the liquidity ratio (current, quick,and cash ratio) of PT. Indo Rama Synthetics, Tbk were in low quality since it was below the industryaverage. Meanwhile the ratio of inventory to net working capital of PT. Indo Rama Synthetics, Tbk wasabove the industry average. Seeing from its solvency ratio like debt to asset ratio, debt to equity ratio,and long term debt to equity ratio, PT. Indo Rama Synthetics was in suf?icient condition because therewas an enhancement of ratio rate per years. However, the results were also remained the same for therate of average industry because it was above the average industry overall.